Comparison of granulated and loose ash in fertilisation of Scots pine on peatland - Hytönen, Jyrki; Hökkä, Hannu (Finnish Society of Forest Science, 2020)
The effects of wood ash fertilisation on tree nutrition and growth on forested peatlands has been studied using loose ash, but in practice, ash fertilisation is done almost exclusively with granulated ash. In this study, the effects of granulated ash and loose ash (both 5 Mg ha–1) on the growth and nutrition of Scots pine (Pinus sylvestris L.) stands were compared between a nitrogen-poor and a nitrogen-rich site over 15 years. On the nitrogen-rich site, wood ash application was also compared with commercial PK fertilisation. On the nitrogen-rich site, mean stand volume growth increase over unfertilised control treatment during the 15 year study period using granulated ash and commercial PK fertiliser was of the same magnitude (on average, 2.2–2.3 m3 ha–1 a–1). However, when loose ash was used growth increase over control was higher (3.7 m3 ha–1 a–1). On the nitrogen-poor site, the mean growth increase gained by loose or granulated ash (1.4–1.5 m3 ha–1 a–1) over the unfertilised control treatment was not significant. Fertilisation with loose ash or PK increased foliar P, K and B concentrations already in the first or second growing season, following fertilisation on both sites. Granulated ash increased foliar P concentrations on the nitrogen-rich site less than loose ash. After an initial increase, foliar P, K and B concentrations decreased at the end of study period. On the nitrogen-poor site, foliar P concentrations were below the deficiency limit by the end of the study period
Keywords: Pinus sylvestris; fertilisation; granulation; nutrition; PK fertiliser; wood ash